The Role of Social Media Influencers in Shaping Consumer Preferences: Trends and Implications for Brand Strategy - Sajili, Mohamad; Rakhmanita, Ani; Pramelani, Pramelani (Equator Journal of Management and Entrepreneurship (EJME), 2024)
This study investigates the role of social media influencers in shaping consumer preferences on the Shopee platform, focusing on the mediating effects of brand awareness and trust. Using a quantitative research design, data were collected from 100 Shopee consumers in Jakarta through random sampling, and analyzed using Smart PLS to assess the relationships between social media influencers, brand awareness, trust, and consumer preferences. The results demonstrate that social media influencers significantly impact consumer preferences both directly and indirectly, through increased brand awareness and enhanced trust. The findings suggest that brand awareness and trust are key mediators in the relationship between influencers and consumer decision-making. This study highlights the importance for brands to strategically collaborate with influencers to optimize their marketing efforts, leveraging influencer credibility to boost consumer engagement and drive purchasing behavior on e-commerce platforms like Shopee. These insights provide valuable implications for brands looking to maximize the effectiveness of influencer marketing in the digital marketplace.